Aseptic Technique. Issue 18 (16th April 2019) - Bykowski, Tomasz; Holt, Jonathan F.; Stevenson, Brian
Abstract: This article describes common laboratory procedures that can reduce the risk of culture contamination, collectively referred as "aseptic technique." Two major strategies of aseptic work are described: using a Bunsen burner and a biosafety cabinet. Both methods are presented in the form of general protocols applicable to a variety of laboratory tasks such as pipetting and aliquotting, preparation of growth media, inoculation, passaging, and spreading microorganisms on petri dishes. © 2019 by John Wiley & Sons, Inc.